Beyond global governance : prospects for global government - Yunker, James A. (University Press of America, 2014)
In these essays, James A. Yunker issues a powerful challenge to conventional thinking on world government. Based on an innovative plan for a limited world government tentatively designated the "Federal Union of Democratic Nations," this book envisions a legitimate world government a quantum leap beyond the United Nations of today.